If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (g * g) + -5 = 125 Multiply g * g (g2) + -5 = 125 g2 + -5 = 125 Reorder the terms: -5 + g2 = 125 Solving -5 + g2 = 125 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + g2 = 125 + 5 Combine like terms: -5 + 5 = 0 0 + g2 = 125 + 5 g2 = 125 + 5 Combine like terms: 125 + 5 = 130 g2 = 130 Simplifying g2 = 130 Take the square root of each side: g = {-11.401754251, 11.401754251}
| 4.2x-55=2.4x+8 | | 5x+9=-x-15 | | 7n+6=64 | | 2y-10=50 | | x(x-3)-30=5(x-2) | | 0=350sin(40)t-16t^2 | | 7x+7.44=4x+12 | | 2y+1/3=7/3 | | 7.6x-2.1x=110 | | 14.79-10.22= | | 32=5e+2p | | -4c+8=-5c+9 | | 3(r/5-5)=-2/5r-20 | | 4=2x+9 | | 2(y-7)/3=-3y | | 9x+6=27x-5 | | 6x+24=2x+84 | | 1/4(5y-3)+1/16(12y+17) | | c-3/3-c+15 | | 39.64+.50x=80 | | 5y-7+y+51=8y+50-4x | | -7=z/3 | | 0.25=(x-75)/x | | 6xy=71.00 | | P(6)=10(6)-7 | | 9=-12+5 | | 24y-11=33-20y | | (5x+7)(5x^2-16x+12)=0 | | 113=11x+3 | | 5x-2=4-25x | | 12.50+6timesy=71.00 | | 7x+5=-114 |